PERSEUS ODV QC software - Ingerov, Andrey; Khaliulin, Alexey Kh; Godin, Eugeny A.; Zhuk, Elena; Isaeva, Elena; Gertman, Isaac; Zodiatis, George; Nikolaidis, Andreas (My University, 2016)
The PERSEUS ODV QC Utility has been developed in the framework of the PERSEUS project.[1] The QC Utility implements a QC procedure for ODV files and assigns QC flags to metadata and data values according to the SEADATANET vocabulary L20. The QC procedure results are QC flags in an ODV file and a log file with a list of possible errors. The QC Utility can operate both in the window and console modes. The QC procedure includes a set of metadata and data quality tests. The metadata tests are: location check, date/time (including velocity and chronology) check and sea depth check. The data tests are based on check arrays (climate, statistics, parameter ranges and thresholds for spikes and gradients check) for sub-regions (local) or the entire region (regional). These arrays are assigned to the P02 parameter codes. The P01 codes are not used because of their superfluity (many codes correspond to the same parameter). The P02 vocabulary is more suitable but it does not provide identification of all parameters. The QC Utility gives a possibility of extending the P02 codes list to identify the parameters more correctly. Data tests include sounding value check (including order check), climatic check (if climatic arrays for the parameter are available), statistic check (if statistic arrays for the parameter are available), range check (if ranges for the parameter are available), fixing density inversions for hydrological data, fixing spikes (if corresponding thresholds for the parameter are available), gradient check (if corresponding thresholds for the parameter are available).
Keywords: PERSEUS; QC flags; QC utility; Quality check